Beyond antioxidants: Selenium and skeletal muscle mitochondria - Wesolowski, Lauren T.; Semanchik, Pier L.; White-Springer, Sarah H. (Frontiers in Veterinary Science, 2022)
The element, Selenium (Se), has an essential nutritive and biological role as a trace mineral known primarily for its vital antioxidant functions as a constituent of the selenoenzyme, glutathione peroxidase. However, Se also has a much more global biological impact beyond antioxidant function. The objective of this review is to present an overview of prior research on the extra-antioxidant effects of Se with a key focus on skeletal muscle mitochondrial energetics. Cognizance of these additional functions of Se is requisite when formulating and recommending dietary supplementation of Se in humans or animals. Chief amongst its myriad of biological contributions, Se influences mitochondrial capacity and function and, subsequently, muscular health. Dietary Se supplementation has been shown to increase skeletal muscle mitochondrial volume density and within some cell lines, Se treatment increases mitochondrial biogenesis and respiratory capacity. In addition, the selenoproteins H, N, W, and O and deiodinases exhibit varying effects on mitochondrial and/or skeletal muscle function. Selenoprotein H enhances mitochondrial biogenesis whereas selenoproteins N and W appear to influence muscle calcium homeostasis which impacts mitochondrial function. Moreover, selenoprotein O’s intramitochondrial residence facilitates Se’s redox function. Deiodinases regulate thyroid hormone activation which impacts muscle cell regeneration, metabolism, and reactive oxygen species production. Although the precise relationships between dietary Se and skeletal muscle mitochondria remain unclear, previous research constitutes a firm foundation that portends promising new discoveries by future investigations.